EFEKTIVITAS DAN KONTRIBUSI PENERIMAAN PAJAK DAERAH TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN BALANGAN TAHUN 2017-2019 - Riswan Haryadi; Sustinah Limarjani; Rina Fariany (Universitas Lambung Mangkurat, 2021)
The purpose of the research is basically to find out more: (1) How effective local tax revenues are for 2017-2019 local revenue. (2) What is the level of achievement of realization targeted by the Balangan Regency Regional Finance Agency during the receipt of Regional Taxes on 2017-2019 Regional Original Revenue.